(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
English is one of the languages that are taught formally in the educational field. At present, the knowledge of the student in English is accelerating. English has become extremely important to the academic, personal, and professional advancements of the student to succeed in their academic performance and perform effectively as a student. English grammar is one of the English competencies that consist of a system of a language that must be comprehended and mastered by the students. Grammar has been one of the difficulties in mastering English language in a country where English is still a foreign language. Many students have a problem in constructing sentences and speaking in English because they think that their grammar is wrong. However, in high school or colleges and maybe in elementary school, students are required to speak in English in different subjects. The descriptive method was used in this study. This study aimed to improve and enhance the pronunciation skills through speech lesson among Grade 12 Accountancy, Business, and Management (ABM)students in Bestlink College of the Philippines. A descriptive study determines and reports the way things are. It comprises the information of all students and present facts regarding the nature and status of anything. The main instrument used was questionnaire, which was used to accumulate the data needed. Scaling was composed of the indicators based on the variables such as difficulties in grammar, advantage in grammar, and other interventions in improving grammar skills. The students showed difficulties on grammar in terms of are the recitation, quizzes, written works, and school activities. The respondents agreed that the other interventions in improving grammar skills included reading English books during free time, watching foreign movies, reading articles with a good English grammar, practicing writing with a basic English grammar, and attending a grammar tutorial. English grammar is extremely difficult to learn and master. Thus, we conducted research on how to improve the grammar skills of Grade 11 ABM students. We want to educate students the proper way of constructing sentences because many students nowadays do not how to speak in English. We also want to prepare them for their professions. Therefore, students need to focus on different English subjects and train themselves on how to speak in English. Parents should also encourage their children to learn more about English grammar.